Global Regularity of 2D Leray-Alpha Regularized Tropical Climate Models (Journal of Partial Differential Equations, 2020)
In this paper, we establish the global regularity of 2D leray-alpha regularized tropical climate models. The global strong solution to the system with a half Laplacian of the first baroclinic model of velocity $(Λ v)$ and thermal diffusion $(-Δθ)$ or with only the dissipation of the barotropic mode $(-Δ u)$ are obtained.
Keywords: Tropical climate model; Leray-alpha model; global regularity.